হিমু মামা - আহমেদ, হুমায়ূন, ১৯৪৮-২০১২ (ঢাকা : অবসর, 2004)
Social novel : family life.
প্রথম প্রকাশ : ২০০৪
Donated by Farhana Zahir, Assistant Professor, BRAC Business School
Keywords: Bengali fiction; Bengali literature